Traquejos e labutas: trabalhadores escravizados no sertão do Piauí (São Raimundo Nonato, segunda metade século XIX) - Viana, Nayanne Magna Ribeiro (2018)
The present work aims to understand how slavery was structured in São Raimundo Nonato, a municipality in the hinterland of Piauí, in the second half of the nineteenth century. This research aims to discuss about the organization of slave labor, the profile of the local captive population, family arrangements, tactics performed by the captives to achieve freedom and the living conditions of freedman. For that end, it was done a crosslink between various sources, such as the post-mortem inventories, records in notary’s offices and parishes, letters and administrative reports, registrations and classification of slaves, among others. That way, it was possible to verify the experience of being enslaved in an area characterized by the practice of livestock and subsistence agriculture, with production focused on supply the internal market.